Impact of personalized cardiovascular disease risk estimates on physical activity-a randomized controlled trial. - Price, H; Griffin, S; Holman, R (2011)
AIM: Informing a person of their individual risk of developing a disease in the future may be sufficient to provide the person with the impetus to adopt risk reducing behaviours. The aim of this study was to determine if a personalised 10-year cardiovascular disease (CVD) risk estimate can increase physical activity and other risk reduction behaviours in adults at high risk of CVD. METHODS: Pilot 2 × 2 factorial randomised controlled trial conducted in Oxfordshire, UK including 194 adults at increased CVD risk (10-year CVD risk ≥ 20%) recruited from four general practices. Main outcome measure at one month was physical activity measured by accelerometer. RESULTS: Median (IQR) age was 62.3 (54.9, 66.1) years, 67% were men and 19% had known diabetes. Mean (SD) total accelerometer counts per day was 297 × 10(-3) (110 × 10(-3) ) and activity of moderate or greater intensity was undertaken for 53 (22) minutes per day. In the 185 (95%) participants attending follow-up an increase in physical activity was not seen. There was a non-significant 0.5% (p = 0.56) greater increase in accelerometer counts in those receiving personalised CVD risk estimates. No significant within or between group changes were seen at one month in estimated 10-year CVD risk. A net 7% decrease in mean LDL cholesterol (p = 0.004) was seen in the intervention group despite similar increases in new prescriptions for lipid lowering therapies. CONCLUSION: In adults at increased risk of CVD provision of personalised 10-year CVD risk estimates did not appear to increase physical activity or estimated CVD risk over a one-month period.